A new homoisoflavan from Dracaena cinnabari Balf. f. resin: α-glucosidase and COX-II inhibitory activity. Issue 5 (4th March 2022) - Helal, Iman E.; Elsbaey, Marwa; Zaghloul, Ahmed M.; Mansour, El-Sayed S.
Abstract: A new homoisoflavan, identified as (3 R )-7-hydroxy-3′, 4′-methylenedioxyhomoisoflavan, was isolated from Dracaena cinnabari Balf. f. resin. The structure was elucidated by one- and two-dimensional NMR spectroscopy as well as high resolution mass spectrometry. In addition, a diverse group of flavonoids were isolated, representing homoisoflavans, flavans, flavanones, chalcones and dihydrochalcones. The compounds were evaluated for their α-glucosidase and COX-II inhibition activity. The obtained IC50 values of the tested flavonoids gave an insight about some key structural features to their α-glucosidase and COX-II inhibitory activity. For α-glucosidase inhibitory activity, a flavanone skeleton was favorable over a flavan. For COX-II inhibition, the introduction of a fused heterocyclic ring at the homoisoflavan skeleton enhanced the activity. Abstract : UF0001